Stones, tablets, and scrolls : periods of the formation of the Bible - Dubovský, Peter; Giuntoli, Federico, 1969- (Mohr Siebeck, 2020)
A constant re-evaluation of the new archaeological and textual material unearthed and edited in recent decades is a recurrent duty of ancient and modern scholars. Since the overwhelming amount of available data and the complexity of new methodologies can be competently handled only by specialized scholars, such a re-evaluation is no longer possible for a single scholar. For this reason, archaeologists, cuneiform and biblical scholars as well as classicists joined forces at an international conference in Rome in May 2017 to share their accumulated knowledge. The results of the proceedings are presented here in the oral stage along with the Assyrian, Babylonian, Persian, and Greco-Roman periods.
" ... collection of papers that were presented during a conference ... held at the Pontifical Biblical Institute in Rome on May 11-13, 2017"--Preface, page [v]
Keywords: Bible. -- Old Testament -- Historiography -- Congresses.; Bible. -- Old Testament -- Antiquities -- Congresses.; Bible. -- Old Testament -- History of contemporary events -- Congresses.; Bible. -- Old Testament -- Criticism, interpretation, etc. -- Congresses.; Bible. -- Old Testament -- History of Biblical events -- Congresses.; Dead Sea scrolls -- Criticism, interpretation, etc.; Dead Sea scrolls; Bible. -- Old Testament; Bible as literature.; Bible (Littérature); History of contemporary events; History of Biblical events; Historiography; Antiquities; Bible as literature; Criticism, interpretation, etc.; Conference papers and proceedings